2019
DOI: 10.1039/c9ra08700a
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of different biochar types on the anaerobic digestion of sewage sludge

Abstract: Pyrolysis temperature and feedstock types had a pronounced effect on biochar properties, and biochar could facilitate the anaerobic digestion process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 73 publications
(89 reference statements)
2
35
0
Order By: Relevance
“…From 2015, numerous studies [13,[20][21][22][23][24][25][26][27][28][29][30] have investigated BC supplementation to enhance methane production during the AD of wastewater sludge, sometimes with controversial results. In most studies, the addition of BCs improved methane yields and production rates to different extents, due to mechanisms such as biomass immobilization, enhanced interspecies electron transfer, mitigation of ammonia inhibition, increased AD buffering capacity, and carbon dioxide sequestration [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From 2015, numerous studies [13,[20][21][22][23][24][25][26][27][28][29][30] have investigated BC supplementation to enhance methane production during the AD of wastewater sludge, sometimes with controversial results. In most studies, the addition of BCs improved methane yields and production rates to different extents, due to mechanisms such as biomass immobilization, enhanced interspecies electron transfer, mitigation of ammonia inhibition, increased AD buffering capacity, and carbon dioxide sequestration [17].…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, the addition of BCs improved methane yields and production rates to different extents, due to mechanisms such as biomass immobilization, enhanced interspecies electron transfer, mitigation of ammonia inhibition, increased AD buffering capacity, and carbon dioxide sequestration [17]. However, additional inhibitory effects on AD were observed in the case of excessive doses of BCs [21,23,24,27,30]. The variability of these results may derive from the extensive variation in BC physic-chemical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Moreover, DIET is faster than IET through H 2 for CH 4 formation. 49 Zhang et al 50 concluded that BC supplementation in anaerobic digestion improved the growth of Methanosarcina compared with H 2 -consuming bacteria (eqn (5)), being in accordance with the higher CH 4 yields in BC-amended bioreactors in comparison to other bioreactors without BC. Gustavsson et al 13 conrmed that Ni or Co was a key element for maintaining bioCH 4 generation process stability and boosted the substrate utilization level.…”
Section: Kinetic Evaluationmentioning
confidence: 82%
“…Nevertheless, when the balance between different functional groups recovered, the reactor's performance also recovered as shown by a decrease in effluent COD and much better COD removal efficiency. Some previous reports have indicated that biochar supplementation could enhance the performance of anaerobic digestion processes in terms of methane production (Wang et al, 2020;Zhang et al, 2019). Specifically, Wang et al (2020) concluded that biochar addition could enhance the methane production rate, and its final yield by increasing buffering capacity and the diversity of methanogens of the anaerobic process.…”
Section: (B)) Particularly Ordermentioning
confidence: 98%